(untitled) (Biological Sciences - PJSIR, 1999)
The statistical analysis of variance for single yarn strength, elongation and rupture per kilometer presented in Table 2 indicates that the effect of different models of ring frames on these parameters is highly significant. The comparison of individual mean values for tensile parameters by Duncan Multiple Range (DMR) test is presented in Table 3. It is clear from the results that the quality of yarn is significantly effected by different makes and models of ring frames and newer models of ring spinning machines definitely produced superior quality yarn. The finding are in agreement with that of Douglas (1989) and it may be concluded that the quality